PENDAMPINGAN LEGALITAS USAHA BAGI PELAKU UMKM DI DESA RIMBO PANJANG, TAMBANG, KAMPAR - Hamdani, Febbyana Wulandari; Utami, Bunga Chintia; Saidi, Julita; Kurnia, Deby; Toruan, Tuty Susanty L.; Septiana , Suci Anggraini; Raja, Muhammad Fathir; Sugito, Marcel Bayu; Yolanda, Alya (Jurnal Abdi Insani, 2025)
A socialization and support program related to business legality for MSME actors in Rimbo Panjang Village, Tambang District, Kampar Regency was held to increase the knowledge and skills of the community in managing Business Identification Numbers (NIB), Home Industry Food (PIRT), and Halal Certification. This activity was carried out due to the low awareness and knowledge of MSME actors regarding the importance of business legality, resulting in many local products lacking official permits and facing difficulties in competing in broader markets. Through participatory socialization and mentoring methods, 13 MSMEs successfully obtained NIBs, 2 MSMEs obtained PIRT distribution permits, and 8 MSMEs received halal certificates. These results indicate that the support provided has a positive impact on improving the legality, quality, and competitiveness of MSMEs. In addition to providing legal certainty, this program also expands market access, opens up investment opportunities, and increases consumer confidence in local products.